Results of tests on the indicator of external noise of electric locomotives in the standing time - M. Yu. Noskov; M. M. Ginshparg; N. S. Nesterov (Вестник Научно-исследовательского института железнодорожного транспорта)
The authors of the Test Loop of the JSC “VNIIZhT” had conducted tests of mainline electric locomotives intended for handling freight trains on sections of the road electrified with alternating current at a voltage of 25 kV (electric locomotives of an alternating current). Tests were conducted in terms of the level of external noise at the standing time. The results of tests of AC electric locomotive, which was in a stationary mode, are presented in terms of the external noise index, and a methodology for performing these tests is described. As a result of the conducted researches, the article establish the main sources of external noise in the operation of AC electric locomotives (fans intended for cooling electrical equipment and traction motors, air compressors, traction transformers, etc.), its actual values, as well as the nature of the sound field around electric locomotives. The analysis of the obtained sound field made it possible to identify the points where the excess of the standard noise values (more than 65 dBA) is observed. It is proposed to bring the technical condition of the equipment, such as traction transformer, converter and cooling module of the traction engine of the power compartment of an electric locomotive in accordance with the normative documentation. The repeated measurements of the external noise level after technical completion did not reveal the excess of its normative values in accordance with the regulatory documentation. In order to provide a normative margin in terms of the external noise of an electric locomotive, it is proposed to use sound-absorbing material in the construction of its body. It is recommended to perform an experimental study of the spectral composition of the noise of the equipment of an electric locomotive operating at the standing time and the resulting external noise at points located outside and around the locomotive in order to calculate the acoustic characteristics of sound-absorbing materials. Sound absorbing material is expedient to be selected depending on the frequency range in which the greatest excess is observed above the maximum permissible values using known empirical and semi-empirical dependences, on the basis of which it is possible to preliminary determine its sound-absorbing properties in the frequency range established by regulatory documents. After equipping the power compartment of the locomotive with soundproof materials, tests on the evaluation of the external noise of an electric locomotive at standing should be repeated.